Old Oswestry Hillfort and Its Landscape - Malim, Tim (Archaeopress, 2020)
This book, organised into 14 well-crafted chapters, charts the archaeology, folklore, heritage and landscape development of one of England's most enigmatic monuments, Old Oswestry Hillfort, from the Iron Age, through its inclusion as part of an early medieval boundary between England and Wales, to its role during World War I.